Origin and early development of the chicken adenohypophysis - Sánchez-Arrones, Luisa; Ferrán, José L.; Hidalgo-Sanchez, Matías; Puelles, Luis (Frontiers in Neuroanatomy, 2015)
The adenohypophysis (ADH) is an important endocrine organ involved in the regulation of many physiological processes. The late morphogenesis of this organ at neural tube stages is well known: the epithelial ADH primordium is recognized as an invagination of the stomodeal roof (Rathke’s pouch), whose walls later thicken and differentiate as the primordium becomes pediculated, and then fully separated from the stomodeum. The primordium attaches to the pial surface of the basal hypothalamus, next to the neurohypophyseal field (NH; future posterior pituitary), from which it was previously separated by migrating prechordal plate cells. Once the NH evaginates, the ADH surrounds it and jointly forms with it the pituitary gland. In contrast, little is known about the precise origin of the ADH precursors at neural plate stages and how the primordium reaches the stomodeum. For that reason, we produced in the chicken a specific ADH fate map at early neural plate stages, which was amplified with gene markers. By means of experiments labelling the mapped presumptive ADH, we were able to follow the initial anlage into its transformation into Rathke’s pouch. The ADH origin was corroborated to be strictly extraneural, i.e., to lie at stage HH4/5 outside of the anterior neural plate within the pre-placodal field. The ADH primordium is fully segregated from the anterior neural border cells and the neighboring olfactory placodes both in terms of precursor cells and molecular profile from head fold stages onwards. The placode becomes visible as a molecularly characteristic ectodermal thickening from stage HH10 onwards. The onset of ADH genoarchitectonic regionalization into intermediate and anterior lobes occurs at closed neural tube stages.